SINERGISITAS KOMISI YUDISIAL DAN MAHKAMAH AGUNG DALAM SISTEM KETATANEGARAAN: SYNERGY OF THE JUDITIONAL COMMISSION AND THE SUPREME COURT IN THE STATE SYSTEM - Shadiq, Muhammad Amil (Clavia, 2022)
The judicial commission and the Supreme Court are constitutionally functionally related when viewed in Articles 24 A and 24 B of the 1945 Constitution of the Republic of Indonesia. To build an ideal relationship between the judicial commission and the Supreme Court in the future, a partnership relationship (partnership) with each institution is needed to maintain their rights and obligations, considering that the judicial commission and the court have been explicitly regulated in Articles 24 A and 24 B of the Law. - Laws of the Republic of Indonesia and the law as elaboration thereof. The importance of eliminating the 'ego' of each institution, this is related to the leadership (leadership) of the leaders of the two institutions.